Entrepreneurial attitudes of Andalusian university students - Francisco Li\~nán Alcalde; Juan Carlos Rodríguez Cohard (European Regional Science Association (ERSA), 2004)
At the present time, the entrepreneur's essential role in the process of regional economic development is generally recognized. A greater degree of entrepreneurial dynamism in a region is usually associated with higher growth rates and development levels in the long run. In particular, there seems to be a greater participation in firm creation processes among highly educated people, as well as those aged 25 to 34 years. Therefore, this segment of the population would be the one with the greatest entrepreneurial potential. It would be a strategic segment for the design of more effective entrepreneurial development measures. In the case of the Spanish region of Andalusia, it has an income level well below the national and, especially, the European Union average. At the same time, the entrepreneurial activity is also one of the lowest nationally. Thus, whether we measure the share of the labour force working for themselves, or the mean size of the firms, both indicators are clearly under to the national average. Therefore, it is interesting to analyze the degree of entrepreneurship of the population or, at least, of that segment with highest entrepreneurial potential. Only starting from an accurate diagnosis will it be possible to act in a really effective way. From this standpoint, the objective of this paper is to know the attitudes of the Andalusian university students towards entrepreneurial activity and the creation of enterprises. Those students are especially relevant, since they belong to that strategic segment of higher entrepreneurial potential individuals. In fact, they are both highly educated and around the age of 25. Besides, universities constitute centres of knowledge and excellence. Therefore, their role in the regional economic transformation should be essential. To achieve that objective we have analyzed the situation of two very different centres within the region. The University of Seville is large (more than 60.000 students), old, and located in the greatest metropolitan area in the region. The University of Jaén is new, small (15.000 students), and located in a medium-sized city. Therefore, the existing differences among them may explain some of the factors that would be influencing those entrepreneurial attitudes. From that viewpoint, universities would play a very significant role in entrepreneurial promotion. Indeed, they cannot only guide their students toward self-employment. They can also offer specific training for the creation and dynamism of enterprises -“entrepreneurial education”-. However, Andalusian universities are playing a very limited role in this field so far. Finally, this work is framed within a research project aimed at contributing to the development of economic policy measures that might be more effective to promote the emergence of new entrepreneurs, especially of more dynamic entrepreneurs. Therefore, this project would move along the lines of reports as that of the European Commission (2003): Green Paper Entrepreneurship in Europe.
Keywords: 330